Design, synthesis and characterization of the electrochemical, nonlinear optical properties and theoretical studies of novel thienylpyrrole azo dyes bearing benzothiazole acceptor groups - Raposo, M. Manuela M. (2011)
Two series of related donor-acceptor conjugated heterocyclic azo dyes based on the thienylpyrrole system, functionalized with benzothiazol-2-yl (5-6) or benzothiazol-6-yl acceptor groups (7) through an N=N bridge, have been synthesized by azo coupling using 1-alkyl(aryl)thienylpyrroles (1) and benzothiazolyl diazonium salts (2-4) as coupling components. Their optical (linear and first hyperpolarizability), electrochemical and thermal properties have been examined. Optimized ground-state molecular geometries and estimates of the lowest energy single electron vertical excitation energies in dioxane solutions were obtained using density functional theory (DFT) at the B3LYP/6-31+G(d,p) level. Hyper-Rayleigh scattering (HRS) in dioxane solutions using a fundamental wavelength of 1064 nm was employed to evaluate their second-order nonlinear optical properties. Of these systems, the benzothiazol-2-yl-diazenes 5-6 exhibit the largest first hyperpolarizabilities ( = 460 - 660 x 10-30 esu, T convention) compared to benzothiazol-6-yl-diazenes 7 ( = 360 - 485 x 10-30 esu, T convention). Good to excellent thermal stabilities were also obtained for all azo dyes (235 - 317 oC). This multidisciplinary study showed that modulation of the optical and electronic properties can be achieved by introduction of the benzothiazole acceptor group in the thienylpyrrole system through position 2 or 6 of the benzothiazole heterocycle.